Espectroscopia de campo-próximo em sistemas bidimensionais - Rodolfo Vieira Maximiano (2012)
A theory describing the near-field Raman enhancement in two-dimensional (2D) systems is presented. The analysis quanties the near-field Raman intensity as a function of the tip-sample distance, Raman polarizability tensor components, incident laser beam configuration, and tip orientation relative to the sample plane. Our results show that the near-field Raman intensity is inversely proportional to the 10th and 8th power of the tip-sample distance in the incoherent and coherent scattering regimes, respectively. Optimal conditions for the tipinclination angle for different congurations are determined, and the results can be used as a guide for TERS experiments in 2D systems, such as graphene and two-dimensional electron gases, and can be extended to opaque bulk materials with at surfaces.